2018
DOI: 10.22214/ijraset.2018.6179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Depth and Orientation on Germination of Yam (Dioscorea) Minisett

Abstract: Adoption of yam minisett technology in mechanization call for a study to ascertain whether planting depth and orientation of yam (Dioscorea alata) in the soil affects germination, since much work has not been done in that regard. Knowledge of the effects of yam minisett planting depth and the orientation in the soil on germination provide useful information for the development of planter since minisett falling from planter could be at any position. A survey was conducted to investigate how germination affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…To mechanize the planting of yam minisett, the potato planter was adopted and modified to suit the planting of yam minisett. The features of minisett (planting material) is a form of sector which has five (5) faces of about 80% fresh and remaining 20% skin [8], unlike potato planting material which has skin all round. Due to the nature of the sett, modification of potato planter included metering mechanism, positioning of hopper, furrow opener and coverer.…”
Section: Methodology a Yam Minisett Physical Properties Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…To mechanize the planting of yam minisett, the potato planter was adopted and modified to suit the planting of yam minisett. The features of minisett (planting material) is a form of sector which has five (5) faces of about 80% fresh and remaining 20% skin [8], unlike potato planting material which has skin all round. Due to the nature of the sett, modification of potato planter included metering mechanism, positioning of hopper, furrow opener and coverer.…”
Section: Methodology a Yam Minisett Physical Properties Measurementmentioning
confidence: 99%
“…The selection and design calculations of the planter components were based on materials specification, soil and yam physical properties. The design of yam minisett planter did not consider the orientation of sett from the hopper into the soil since results from Arkoh and Bobobee [8] confirmed that healthy sett germinates so far as soil touches the skin of the minisett. However, the following considerations were made:…”
Section: B Design Principles and Requirement Of The Plantermentioning
confidence: 99%